(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
Tourism is currently one of the most important sectors for the economic development of the Republic of Croatia. It mainly focuses on foreigners from within the EU. Because of the dynamic and very competitive tourist market, it is hard to forecast foreign tourism demand nowadays. It can vary over time among tourists of different nationalities. Stability of inbound tourist demand forms an important condition for the development of tourism and foreign currency income. Considering that tourism policy-makers must distribute available resources to different tourism markets for use in promotion, the purpose of this study is to analyze, by country of origin, the number of overnight stays by inbound foreign tourists in accommodation establishments as well as their average daily spending in Croatia and to construct an optimal mixture of tourists of different nationalities that will help tourism policy-makers to optimize or maximize tourism revenues at a certain level of risk. The main idea of this research is to apply financial portfolio theory to Croatian tourism demand and to construct an optimal mixture of foreign inbound tourists when there is an infinite number of possibilities. Several optimal mixes were calculated with different risk/return options to show on which foreign tourist markets Croatia must focus. For example, to achieve the mixture of foreign tourists that provides the highest level of tourist consumption expenditures, tourism authorities should increase their resources on the German, Slovenian, Italian and Austrian markets. The results of this research can easily be modified according to policy maker’s risk/return preferences.